Synchronous centennial abrupt events in the ocean and atmosphere during the last deglaciation - Chen, Tianyu; Robinson, Laura F.; Burke, Andrea; Southon, John; Spooner, Peter; Morris, Paul J.; Ng, Hong Chin (Science, 2015)
This study was funded by the European Research Council, the Philip Leverhulme Trust, the National Science Foundation and a Marie Curie Reintegration Grant. Antarctic ice-core data reveal that the atmosphere experienced abrupt centennial increases in CO2 concentration during the last deglaciation (~18-11 thousand years, ka). Establishing the role of ocean circulation in these changes requires high-resolution, accurately-dated marine records. Here we report radiocarbon data from uranium-thorium dated deep-sea corals in the Equatorial Atlantic and Drake Passage over the last 25 ka. Two major deglacial radiocarbon increases occurred in phase with centennial atmospheric CO2 rises at 14.8 ka and 11.7 ka. We interpret these radiocarbon-enriched signals to represent two short-lived (<500 years) ‘overshoot’ events with Atlantic meridional overturning stronger than modern. These results provide compelling evidence for a close coupling of ocean circulation and centennial climate events during the last deglaciation Peer reviewed